Composite Laguerre pseudospectral method for Fokker-Planck equations - Wang, Chuan; Wang, Tianjun; Shang, Youlin (Mathematical Modelling and Analysis, 2023)
A composite generalized Laguerre pseudospectral method for the nonlinear Fokker-Planck equations on the whole line is developed. Some composite generalized Laguerre interpolation approximation results are established. As an application, a composite Laguerre pseudospectral scheme is provided for the problems of the relaxation of fermion and boson gases. Convergence and stability of the scheme are proved. Numerical results show the efficiency of this approach and coincide well with theoretical analysis.